2015
DOI: 10.11604/pamj.2015.20.244.4488
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in children with juvenile idiopathic arthritis: effect of dietary intake of macronutrient: results from a cross sectional study

Abstract: IntroductionThe aim of this study was to evaluate the relationship between macronutrient intake, body composition (lean body mass and fat mass) and bone mineral content in Moroccan children with juvenile idiopathic arthritis (JIA).MethodsA cross-sectional study, conducted between May 2010 and June 2011, covering out patient with JIA. The characteristics of patients were collected. The nutritional status was assessed by a food questionnaire including data of food intake during 7 consecutive days using 24-hour d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…JIA patients tend to present body composition and growth impairment due to disease activity, medication, reduced physical activity, and/or malnutrition [ 1 , 8 , 15 ]. Growth impairment is common among JIA patients, ranging from retarded growth to local acceleration of growth in the body part affected, associated with increased production of pro-inflammatory cytokines (interleukin-1β-IL-1β, tumor necrosis factor-α-TNF-α, and interleukin-6-IL-6) [ 16 ].…”
Section: Body Composition and Dietary Challenges In Jiamentioning
confidence: 99%
See 1 more Smart Citation
“…JIA patients tend to present body composition and growth impairment due to disease activity, medication, reduced physical activity, and/or malnutrition [ 1 , 8 , 15 ]. Growth impairment is common among JIA patients, ranging from retarded growth to local acceleration of growth in the body part affected, associated with increased production of pro-inflammatory cytokines (interleukin-1β-IL-1β, tumor necrosis factor-α-TNF-α, and interleukin-6-IL-6) [ 16 ].…”
Section: Body Composition and Dietary Challenges In Jiamentioning
confidence: 99%
“…A cross-sectional study conducted with Moroccan JIA patients (n = 33) evaluated the relationship between macronutrient intake (using 7-day 24-hour recall), body composition, and bone mineral content (using DXA total body measurements) [ 15 ]. The study showed a positive correlation between carbohydrate intake and lean body mass, but dietary intake did not influence fat mass and bone mineral content [ 15 ].…”
Section: Body Composition and Dietary Challenges In Jiamentioning
confidence: 99%
“…Останніми роками досягнуто значних успіхів у вивченні особливостей їх патогенезу та клінічного перебігу, розширилися діагностичні й лікувальні можливості в сфері дитячої ревматології. Однак, незважаючи на це, лікування РХ залишається далеко не завжди ефективним [1]. Хронічний перебіг захворювань, як і лікарські засоби, що використовуються як базисні препарати, мають цілу низку побічних ефектів, які сукупно призводять до серйозних порушень в організмі, затримки росту, статевого розвитку, а нерідкодо тяжких необоротних нутритивних розладів, які, в свою чергу, можуть обумовлювати прогноз і наслідки…”
unclassified